Evaluation Of Manual Patient Handling Activityto Reduce Musculoskeletal Disorders Withmovement And Assisstance On Hospital Patient(study Case R.s Muhammadiyah Bandung) - Amanda Puspita Permata Sari; Rino Andias Anugraha; Yusuf Nugroho Doyo Yekti (eProceedings of Engineering, 2015)
Abstract Handling activities tend to raise a risk of musculoskeletal disorders or MSDs when it implement with wrong method. One of handling activities which have a high risk of MSDs is nursing activity. This study aims to assess the risk of MSDs among nurses in different wards on Muhammadiyah hospital by means of MAPO (Movement and Assistance of Hospital Patient) method. The study was conducted in 13 sections of Muhammadiyah subspecialty hospital including 111 wards. Exposed nursing staff (N=30) were asked to report MSDs experiences in the past one year. The results indicated that 3 units are on the red category, 6 units are on the yellow category, and 4 units come on green category. Lifting factor indicates the high level of patient handling activity. However minor factor aids showed very bad results. We can conclude this activity raises the risk of MSDs for nurses. The other factors such environmental about 27%, training factor 35% and also wheelchair factor 43% need to meet the best requirement to perform the proper handling activity on every ward. It is therefore necessary to implement an ergonomic program in order to modify the observed baneful condition as soon as possible.. Kata kunci : manual handling, patient handling, MAPO Index, movement and assistance of hospital patient, musculoskeletal disorders